2015
DOI: 10.1007/s13304-015-0311-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of post-cholecystectomy bile duct injuries: referral patterns and factors influencing early and long-term outcome

Abstract: Cholecystectomy-related bile duct injuries (BDI) remain a cause of significant morbidity and debate concerning optimal management is ongoing. We reviewed our experience with surgical management of BDI to assess patterns of referral along with postoperative and long-term outcomes. During September 1996-August 2013, 35 patients were operated in our tertiary care center for a Bismuth-Strasberg grade >A BDI after a cholecystectomy performed elsewhere. Injury grade distribution was as follows: D, n = 3; E1, n = 4; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
11
0
3
Order By: Relevance
“…Furthermore, inflammatory changes in the surgical bed produce tissue friability, resulting in increased technical difficulty at repair time [ 38 , 73 ]. In similar, in our study, sepsis at referral due to biliary peritonitis or severe cholangitis was significant predictor of early and late morbidities, despite our aggressive management of it before doing the definitive repair, similarly, it was independent predictor of complications and anastomotic failure after primary repair in Dominguez-Rosado et al, 2016 [ 19 ] study and was predictor of severe complications in Patrono et al, 2015 [ 4 ] study and it was the only independent predictor of major morbidity and a significant predictor of late biliary stricture in Sulpice et al, 2014 [ 31 ] study, in the same line, it was independent predictor of long-term complications in Huang et al, 2014 [ 38 ] study. In the same way, Schmidt et al, 2005 [ 21 ] found that the presence of active peritonitis was independently associated with long-term complications, such as anastomotic stricture, or secondary biliary cirrhosis.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Furthermore, inflammatory changes in the surgical bed produce tissue friability, resulting in increased technical difficulty at repair time [ 38 , 73 ]. In similar, in our study, sepsis at referral due to biliary peritonitis or severe cholangitis was significant predictor of early and late morbidities, despite our aggressive management of it before doing the definitive repair, similarly, it was independent predictor of complications and anastomotic failure after primary repair in Dominguez-Rosado et al, 2016 [ 19 ] study and was predictor of severe complications in Patrono et al, 2015 [ 4 ] study and it was the only independent predictor of major morbidity and a significant predictor of late biliary stricture in Sulpice et al, 2014 [ 31 ] study, in the same line, it was independent predictor of long-term complications in Huang et al, 2014 [ 38 ] study. In the same way, Schmidt et al, 2005 [ 21 ] found that the presence of active peritonitis was independently associated with long-term complications, such as anastomotic stricture, or secondary biliary cirrhosis.…”
Section: Discussionsupporting
confidence: 70%
“…Performing the definitive operation immediately (during the 1st 72 h), in the intermediate period (between 72 h and 1.5 months) or in the late period (after1.5 months) from injury, did not have any significant effect on our late biliary morbidity. Similarly, it did not influence postoperative morbidity in Pottakkat et al, 2010 [ 3 ], Patrono et al, 2015 [ 4 ], Bansal et al, 2015 [ 36 ], Huang et al, 2014 [ 38 ], Kirks et al, 2016 [ 83 ], and Perera et al, 2011 [ 84 ], studies. However, most authors advice late repair of LC-BDIs (≤6 weeks) from LC [ 29 , 53 , 85 ]; this allows the abdominal inflammation to subside prior to definitive repair leading to its success [ 50 , 86 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…1% of the whole cases which may indicate to be a risk factor for BDI. Patrono and his colleagues showed that acute cholecystitis is a nonsignificant trend in cases with BDI and biliary strictures [5] . This can be attributed to the difficulty in identifying the biliary anatomy and also the delay in conversion to open may play another role in BDI.…”
Section: Discussionmentioning
confidence: 99%